Bioinformatics Analysis of HSP90 in Amniotic Fluid and Amniotic Membrane Cells as A Potential Anticancer Drug Target - Hakimeh Zali (Journal of Global Pharma Technology, 2017)
HSP90AA is a crucial protective chaperon protein in normal and cancer cell. It has been previously determined HSP90AA down regulate in tumor cell treated with extract of amniotic membrane (AM) stem cells. Aim of this study find out the pathways and molecules associated with reduction of HSP90AA by bioinformatics methods. Network analysis defined the principal functions of HSP90AA in cancer survival and proliferation through interaction with important proteins with different functions such as AR, AKT, HIF1A and P53 to promote tumor cell proliferation and angiogenesis. Gene ontology analysis released the regulation of nitric oxide synthesis activity. In sum up results distinguished the misexperssion of HSP90AA may due to down-regulation of its transcription factors or systemic changes in gene expression of cancer cell after treated with extract of AM cells and induce apoptosis in oxidation state.Keywords: Hsp90AA, Cancer, Amniotic membrane, Epithelialstem cells, Mesenchymalstem cells, Apoptosis